Heavy Metal Bioaccumulation in Seagrass and Sargassum Across Indonesian Coastal Waters: Ecological Risks and Implications for Sustainable Coastal Management: A Systematic Review - Nur Cholis; Gemala Madumetha; Kusuma Wijaya; Lily Viruly; Nancy Willian (Jurnal Zarah, 2026)
Heavy metal contamination poses a significant threat to Indonesian coastal ecosystems, particularly seagrass meadows and brown seaweeds such as Sargassum, which function as primary producers and environmental bioindicators. This study systematically reviews heavy metal accumulation in seagrass and Sargassum in Indonesian waters and examines its ecological and management implications. A systematic literature review was conducted following the PRISMA 2020 framework, covering studies published between 2016 and 2025 from Scopus, ScienceDirect, Web of Science, Google Scholar, and Garuda. Articles were included if they reported empirical data on heavy metal contamination in seagrass or Sargassum in Indonesia. After screening and quality assessment, 20 studies were selected for thematic synthesis. The results show that lead (Pb) and cadmium (Cd) were the most frequently reported metals exceeding quality standards, identified in 14 of 20 studies. Mercury (Hg) was detected at several sites, while nickel (Ni) and iron (Fe) were mainly associated with mining areas. Higher accumulation was observed in seagrass leaves and Sargassum thalli, particularly in areas influenced by ports, industry, tourism, settlements, and mining. These findings indicate potential ecological risks, including reduced primary productivity and trophic transfer. Overall, seagrass and Sargassum demonstrate strong potential as biomonitors of heavy metal contamination in Indonesian coastal waters.